Parental feeding practices and child eating behavior in different socioeconomic neighborhoods and their association with childhood weight. The STEPS study - Tarro Saija; Lahdenperä Mirkka; Vahtera Jussi; Pentti Jaana; Lagström Hanna (Elsevier Ltd, 2022)
Child obesity risk, child eating behavior and parental feeding practices show a graded association with individual level socioeconomic status. However, their associations with neighborhood socioeconomic disadvantage are largely unknown. In this study (n = 682), we investigated how parental feeding practices and child eating behaviors were associated with body mass index and risk of overweight at preschool age in affluent and disadvantaged neighborhoods. We found that high food approach tendency in disadvantaged neighborhoods predicted higher body mass index and increased the risk of overweight at the age of 6 years compared with affluent neighborhoods. Our results suggest that children's eating habits may have stronger impact on overweight risk in disadvantaged than in affluent neighborhoods.